Optimizing Forms and Size of Windows for Energy Conservation - Sergeychuk, Oleg; Martynov, Viacheslav; Virchenko, Gennadii; Usenko, Iryna (International Journal of Engineering and Technology, 2018)
The article deals with the problem of optimizing the form and size of the windows. This is important because of significant losses of heat through windows. The article demonstrates how to improve methods accepted as standard in Ukraine for calculating the natural illumination and insolation of houses.